Poverty and intra-household resource allocation in Surinamese households - Jeetendra Khadan; Eric Strobl; Theophiline Tuffour (Inter-American Development Bank (IDB), 2020)
This paper examines the allocation of resources of poverty rates within households in Suriname. To this end we employ a bargaining model estimation framework that allows one to identify the allocation of resources across adult and children males and females. Our results using the Suriname 2016/2017 Survey of Living Conditions show that there are considerable differences between men and women, but that there is no gender bias among children. We also find that children are least poor members of households.
Keywords: D12; D13; I31; I32; J12; J13; 330; collective model; intra-household inequality; poverty; resource shares; Suriname